2003
DOI: 10.1002/mabi.200390024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Complexing Polyanions on the Thermostability of Basic Proteins

Abstract: Lysozyme (Lyz), chymotrypsinogen (Cht), and glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) were used as model proteins capable of forming water‐soluble polyelectrolyte complexes with linear synthetic polyanions. The complex formation with sodium poly(methacrylate) (PMA), sodium poly(acrylate) (PAA), sodium poly(anetholsulfonate) (PAS), and potassium poly(vinylsulfate) (PVS) markedly reduced the temperature of protein denaturation, Tmax, as determined by differential scanning calorimetry (DSC). The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
51
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 22 publications
11
51
1
1
Order By: Relevance
“…The transition temperatures of b-lg (Table 1) were decreased by the presence of CMP in the mixed systems. The decrease in denaturation temperature on mixtures of proteins has been ascribed to complex formation by electrostatic interactions (Ivinova, Izumrudov, Muronetz, Galaev, & Mattiasson, 2002;Martinez et al, 2009). Electrostatic interactions have been reported to perturb the structure of myoglobulin and bovine serum albumin causing decreased thermal stability (Imeson, Ledward, & Mitchell, 1977).…”
Section: Size Distribution Of Particles At Ph 35mentioning
confidence: 98%
“…The transition temperatures of b-lg (Table 1) were decreased by the presence of CMP in the mixed systems. The decrease in denaturation temperature on mixtures of proteins has been ascribed to complex formation by electrostatic interactions (Ivinova, Izumrudov, Muronetz, Galaev, & Mattiasson, 2002;Martinez et al, 2009). Electrostatic interactions have been reported to perturb the structure of myoglobulin and bovine serum albumin causing decreased thermal stability (Imeson, Ledward, & Mitchell, 1977).…”
Section: Size Distribution Of Particles At Ph 35mentioning
confidence: 98%
“…It was suggested that similar destabilisation may occur for other proteins upon interaction with highly charged polymeric compounds or surfaces. However, some studies also show that complexation of the protein with a polysaccharide can preserve the functionality of the protein and prevent denaturation (Burova, Varfolomeeva, Grinberg, Haertle´, & Tolstoguzov, 2002;Ivinova, Izumdurov, Munoretz, Galaev, & Mattiasson, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Various experimental methods could be used for studying the formation and properties of such complexes. For example, the influence of complexation between small proteins and negatively charged polyelectrolytes on thermodynamic stability of proteins was investigated by means of differential scanning calorimetry [7]. In that study lysozyme, chymotrypsin and glyceraldehyde-3-phosphate dehydrogenase were used as model proteins, while as negatively charged polyelectrolytes poly(acrylic) acid (PAA), poly(methacrylic) acid (PMA), poly(N-ethyl-4-vinylpyridinium) bromide (PEVP), sodium poly(anetholesulfonate) (PAS), potassium poly(vinylsulfate) (PVS), sodium poly(styrene sulfonate) (PSS) were used.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6]. If instead of a polyelectrolyte a protein is used, the formed complexes are commonly called protein-polyelectrolyte complexes [7][8][9][10][11][12][13][14]. Various experimental methods could be used for studying the formation and properties of such complexes.…”
Section: Introductionmentioning
confidence: 99%